PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN EFIKASI DIRI TERHADAP INTENSI BERWIRAUSAHA MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JAMBI - Hidayatul Arief (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractThis study aims to determine the effect on entrepreneurship education and self-efficacy of entrepreneurial intentions of the students in the Faculty of Teacher Training and Education, Jambi University. This research used a quantitative method using path analysis and Sobel test. A set of questionnaire was utilized in this study as the main data collection. This study involved the students at the Faculty of Teacher Training and Education Jambi University as the subject of the research who took entrepreneurship courses. The sample used in this study was 193 students after being calculated by using the slovin formula. The result of this study indicated that entrepreneurship education and self-efficacy had a positive and significant direct effect on entrepreneurial intention. Furthermore, entrepreneurship education also had an indirect effect on entrepreneurial intentions through self-efficacy.Keywords: Entrepreneurial Intentions, Entrepreneurship Education, Self-Efficacy.